Notes on a Russian four-part icon - Ruzsa, György (Slavica, 2024)
The study analyses a 19th century four-part Russian icon primarily from iconological viewpoints. In the upper left compartment of the icon the depiction of the Theotokos can be seen as the “Softener of Evil Hearts” (Russian: “Умягчение злых сердец”). Another name for it is “The icon of Simeon’s Prophecy” (Russian: “Симеоново проречение”). In the upper right field of the icon a high priest is shown in an open coffin (perhaps Metropolitan Nicephorus of Kiev (†1121)). In the lower left part of the icon Saint Nicholas appears with Christ and the Mother of God. In the lower right field of the icon, the Metropolitan Saint Alexius is painted in the middle, with Saints Catherine on his right and Alexandra on his left.